THE ESSENCE OF THE SERVICES MARKET IN REGIONAL ENTREPRENEURSHIP (International scientific-electronic journal “Pioneering studies and theories”, 2026)
This article discusses the fact that today services constitute an important component of the development of our country and local regions, the integrated services market covers a wide range of relations related to the provision of household, educational, medical, technical, municipal, cultural, communication, transport, consulting, engineering, leasing and other services to the population, and the essence of the services market in regional entrepreneurship.